2010
DOI: 10.1186/1477-7819-8-39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of limb function after various reconstruction methods according to tumor location following resection of pediatric malignant bone tumors

Abstract: Background: In the reconstruction of the affected limb in pediatric malignant bone tumors, since the loss of joint function affects limb-length discrepancy expected in the future, reconstruction methods that not only maximally preserve the joint function but also maintain good limb function are necessary. We analysis limb function of reconstruction methods by tumor location following resection of pediatric malignant bone tumors. Patients and methods:We classified the tumors according to their location into 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 41 publications
0
35
0
2
Order By: Relevance
“…There have been attempts to improve joint function in patients with osteosarcoma by performing an intercalary resection that preserves the native joint [15,17,23,28]. However, this is not easy to do for a juxtaarticular osteosarcoma owing to possible residual tumor if the tumor is close to the articular surface.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been attempts to improve joint function in patients with osteosarcoma by performing an intercalary resection that preserves the native joint [15,17,23,28]. However, this is not easy to do for a juxtaarticular osteosarcoma owing to possible residual tumor if the tumor is close to the articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…Early histologic studies [13,25] of resected specimens and an imaging study [12] have suggested that the prevalence of transepiphyseal spread of the tumor in metaphyseal osteosarcomas is approximately 80%. Some orthopaedic surgeons would prefer treating osteosarcoma penetrating the growth plate by removing the entire epiphysis with the tumor to ensure adequate margins unless the joint is contaminated with tumor, in which case an extraarticular resection is preferred [21,22,28]. However, subsequent replacement with a tumor prosthesis or osteoarticular allograft is associated with uncertain durability of the reconstruction and the longevity of these limb salvage procedures is unlikely to last the lifetime of the patient [3,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations